Application of Neuroscience in Establishing Character Education in Early Children at Aisyiyah 06 Jaten Kindergarten Students - Sari, Nur Novita; Fauziyah, Nur (Universitas Muhammadiyah Surakarta, 2023)
This article aims to review character education in early childhood through the application of neuroscience. The research method used is descriptive qualitative method. Data collection techniques using observation, interviews, and documentation. Neuroscience is the scientific study of the nervous system. In fact, early childhood neuroscience is a golden period in the process of human development. In neuroscience there is the development of intelligence and morality for students. Thus students can optimally optimize the brain network system at an early age to develop their character. Teachers at Aisyiyah 06 Jaten Kindergarten need efforts to instill character education values in students. Through the application of neuroscience, children are given the opportunity to build knowledge through the learning process. The application of this neuroscience also has the potential to develop the character of Islamic education in Aisyiyah 06 Jaten Kindergarten.